Semantic Web For Targeted Retrievals - Ketheeswaren, S. (Rev. Jacob Memorial Christian College, 2008)
The paper introduces the main concepts and principles of the Semantic Web (SW). Paper is structured into, (1) "Technology of Semantic Web which provides a high-level description, with examples, of the main standards and concepts: extensible markup language (X M L). (2) Resource Description Framework (RD F), which is described with some models. (3) Ontologies and their utility in information retrieval, describing best sample ontology for Library and Information Science. By briefing out the above structure, we fi nd SW is pin-targeting to related branches of information more effectively.
Keywords: Semantic web; Resource Locator; RDF